(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this work, we present a novel subclass of bi-univalent functions defined by MeixnerPollaczek and Bell polynomials. Deriving coefficient estimates is the primary focus, especially for the second and third Taylor-Maclaurin coefficients; a2 and a3. Fekete-Szeg¨o functional inequalities related to these subclasses are also examined. By extending and generalizing current subclasses, the proposed class offers fresh perspectives on the geometric and analytic characteristics of biunivalent functions. Our findings demonstrate the theoretical originality and possible uses of orthogonal-polynomial-based functions classes.